1999
DOI: 10.1038/15256
|View full text |Cite
|
Sign up to set email alerts
|

Blocking both signal 1 and signal 2 of T-cell activation prevents apoptosis of alloreactive T cells and induction of peripheral allograft tolerance

Abstract: The alloimmune response against fully MHC-mismatched allografts, compared with immune responses to nominal antigens, entails an unusually large clonal size of alloreactive T cells. Thus, induction of peripheral allograft tolerance established in the absence of immune system ablation and reconstitution is a challenging task in transplantation. Here, we determined whether a reduction in the mass of alloreactive T cells due to apoptosis is an essential initial step for induction of stable allograft tolerance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
527
5
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 707 publications
(564 citation statements)
references
References 24 publications
28
527
5
4
Order By: Relevance
“…The importance of apoptosis induction for peripheral transplantation tolerance has been demonstrated in recent reports [26,49]. Wells et al showed that mice transgenic for bcl-x L expression in T cells or IL-2 deficient mice are resistant to the induction of transplantation tolerance due to defective passive or active T cell apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of apoptosis induction for peripheral transplantation tolerance has been demonstrated in recent reports [26,49]. Wells et al showed that mice transgenic for bcl-x L expression in T cells or IL-2 deficient mice are resistant to the induction of transplantation tolerance due to defective passive or active T cell apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…To address this in our protocol for inducing mixed chimerism and tolerance, we treated B6 mice with our standard regimen (3 Gy TBI, anti-CD8 mAb, 20 Â 10 6 B10.A BMCs, and MR1) and compared the incidence of chimerism and the deletion of donor-reactive CD4 + T cells with that in a group receiving the same protocol plus daily CsA treatment (20 mg/kg) beginning on the day of BMT and continuing for 14 days. This CsA dosing regimen has been shown by other groups to impair allograft survival in mice receiving costimulatory blockade (2,21). In recipients of the standard regimen, 80% of the mice demonstrated long-term multilineage chimerism for at least 27 weeks post-BMT ( Figure 1A).…”
Section: Resultsmentioning
confidence: 80%
“…All chimeric WT animals accepted donor skin grafts >200 days (top), while rejecting third party grafts (bottom), whereas all Bcl-x L recipient mice rejected both donor and third party grafts. (2,39,40), has been reported to be detrimental to the prolongation of graft survival in various protocols using costimulatory blockade (2,21,22). One critical function of calcineurin is the dephosphorylation and activation of NFAT, a key transcription factor involved in the production of IL-2 (41), which promotes FAS-mediated AICD by down-regulating the amount of FLIP, the down-regulator of apoptosis, associated with the Fas molecule (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations